2013
DOI: 10.1149/2.014402jss
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fluorinated Silicon Nitride Gate Insulator on Positive Bias Stability toward Highly Reliable Amorphous InGaZnO Thin-Film Transistors

Abstract: For gate insulator of amorphous InGaZnO thin-film transistor, we fabricated fluorinated silicon nitride (SiN:F) film formed by an inductively-coupled plasma enhanced chemical vapor deposition method by utilizing SiF4/N2 as source gases. Threshold voltage shift against electrical stress was successfully suppressed. Chemical analysis revealed that the hydrogen concentration was reduced to 1/10 of conventional SiN film and fluorine was introduced into the interface between the SiN:F film and channel layer. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…When the postannealing time was increased from 1 to 5 h, V th after 10 4 s PBS reduced from 4.3 to 3.5 V. In order to investigate the causes of the phenomenon, the density of state (DOS) of the front channel interface (D i ) with the PBS duration was evaluated. Low-high C-V measurement is one of the most popular techniques for analyzing semiconductor/insulator interface properties [13], [20]. However, these capacitancebased extraction methods cannot provide the properties of defects, such as trap time constant, and capture cross section.…”
Section: Methodsmentioning
confidence: 99%
“…When the postannealing time was increased from 1 to 5 h, V th after 10 4 s PBS reduced from 4.3 to 3.5 V. In order to investigate the causes of the phenomenon, the density of state (DOS) of the front channel interface (D i ) with the PBS duration was evaluated. Low-high C-V measurement is one of the most popular techniques for analyzing semiconductor/insulator interface properties [13], [20]. However, these capacitancebased extraction methods cannot provide the properties of defects, such as trap time constant, and capture cross section.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first announcement of a-IGZO TFT in 2004 [5], its instability against the bias stress was regarded as a severe problem, and a lot of studies have be done by the worldwide researchers [3,4,[6][7][8][9][10][11][12][13][14][15]. It is well known that the properties of oxide semiconductor are highly dependent on the oxygen content, since oxygen vacancies provide the free carriers.…”
Section: Issues and Prospect Of The Oxide Tftmentioning
confidence: 99%
“…To improve the stability against PBTS, many studies have been reported [9][10][11][12]. The effects of the passivation, annealing process, the condition control of the interface between oxide semiconductor and gate insulator, or the hydrogen content control of the neighboring films [7][8][9][10][11][12]. We also try to improve the BTS stability by optimizing the TFT fabricating process.…”
Section: Reliabilitymentioning
confidence: 99%
“…It is reported that fluorine incorporated into the a-IGZO TFT can effectively improve TFT reliability [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ], because F has several advantages: (i) it has the highest electron affinity among chemical elements, which makes F simple to bond with misoriented metal atoms in the IGZO active layer and reduce the DOS, (ii) compared to hydrogen, F can provide stronger bonding with the metal ion in the active layer to improve the a-IGZO TFT stability [ 27 ], and (iii) extra free electrons can be generated by the fluorine ions by replacing the oxygen sites, due to the difference in electrovalence between the oxygen ion (O 2− ) and the fluorine ion (F − ). The higher electron density induced in the active layer will improve the carrier mobility of the a-IGZO TFT [ 28 ].…”
Section: Introductionmentioning
confidence: 99%